Teachers Choosing Rich Tasks: The Moderating Impact of Technology on Student Learning, Enjoyment, and Preparation. (June 2014) - Aubusson, Peter; Burke, Paul; Schuck, Sandy; Kearney, Matthew; Frischknecht, Bart
This article reports on the pioneering use in education of Discrete Choice Experiments (DCEs) to assess teachers' decisions regarding deployment of rich tasks. The incorporation of this quantitative method into what is usually considered the domain of qualitative researchers is an innovative feature of this study. The DCEs enabled rigorous, reliable, and efficient investigation of the relationships between attributes of the complex environment in which teachers operate. The findings articulate the choices made by teachers related to rich task pedagogy, technology use, and other resources. Understanding the influences on these choices will inform the adoption and adaptation of productive technologies, improve dissemination of good practices, and enhance the design of digital technologies, resulting in better student learning outcomes.